Les Méthodes Multigrilles pour Les Inéquations Quasi Variationnelles Elliptique - belouafi, mohammed Essaid (جامعة الوادي - University of Eloued, 2023)
In this dissertation, multigrid methods have been investigated for solving certain classes of obstacle problems. In the first part of this thesis, we investigated the solution of elliptic quasi-variational inequalities arising in discretization by the finite element method, in this case, we have chosen a linear right-hand side and the variational form associated with linear operator. For these problems, we have proposed a standard multigrid approach for solving a linear system obtained. Otherwise, we have proposed a nonlinear multigrid method for elliptic quasi-variational inequalities with nonlinear source terms and nonlinear variational form. The L-norm convergence of these two approaches has been constructed which demonstrates that the multigrid method has a contraction number with respect to the L-norm. Numerical results which demonstrate the high efficiency of these methods are given for a quasi-variational inequality arising from impulse control problem on a domain with nonpolygonal boundaries. From these numerical results, we have seen that the multigrid method proves to be more efficient than the other iterative methods. في هذه الأطروحة، تمت دراسة الطريقة متعددة الشبكات لحل المتراجحات الشبه تغايرية الناقصية اين يتعلق الحل بالحاجز, في هاته المسألة اخترنا شكل تغايري يتعلق بمؤثر خطي, ثم اعتمدنا على طريقة العناصر المنتهية لاستخراج الشكل المتقطع لهاته المسألة. إستعملنا الطريقة متعدد الشبكات لحل النظام الخطي الذي تم الحصول عليه. ثم اقترحنا طريقة غير خطية متعددة الشبكات لحل المتراجحات الشبه تغايرية الناقصية الغير خطية. تم إنشاء التقارب المنتظم للتقديرين المُقترحين مما يثبت أن الطرق متعددة الشبكات لها رقم تقلص مُتعلق بالمعيار المنتظم. النتائج العددية التي تأكد ما أثبتناه نظرياً مطبقة على متراجحة شبه تغايرية ناقصية متعلقة بمشاكل التحكم. من هذه النتائج العددية ، رأينا أن الطريقة متعددة الشبكات أثبتت أنها أكثر كفاءة من الطرق التكرارية الأخرى.
في العلوم الدقيقة Analyse Mathématique et Apllications أطروحة دكتوراه تخصص
Keywords: Finite element method, Quasi-Variational Inequalities, HJB Equation, Newton’s method, Multigrid Method.; متراجحات شبه تغايرية ناقصية، طريقة العناصر المنتهية، معادلة HJB، الطريقة متعددة الشبكات، طريقة نيوتن.